Behavior Disorder and Social Function Impairment in Children with Basal Ganglia Germ Cell Tumors - Lv W (Dove Medical Press, 2021)
Wenyi Lv,1 Jin Feng,1 Li Chen,1 Shuai Liu,1,2 Xiaoguang Qiu1,2 1Department of Radiation Oncology, Beijing Tiantan Hospital, Capital Medical University, Beijing 100070, People’s Republic of China; 2Beijing Neurosurgical Institute, Capital Medical University, Beijing 100070, People’s Republic of ChinaCorrespondence: Xiaoguang Qiu; Shuai LiuBeijing Neurosurgical Institute, Capital Medical University, No. 119, South 4th Ring West Road, Fengtai District, Beijing 100070, People’s Republic of ChinaTel/Fax +86 1059975266; +86 1059975580Email qiuxiaoguang@bjtth.org; s.liu@bjtth.orgPurpose: Basal ganglia intracranial germ cell tumors (iGCTs) can specifically destroy the basal ganglia network, leading to several cognitive, learning, behavioral, and social impairments. This study aimed to investigate the behavior and social disorders of patients with basal ganglia iGCTs.Patients and Methods: We recruited 30 newly diagnosed iGCTs patients (and their parents) for the current study. The Child Behavior Checklist/6– 18 was used to evaluate emotional and behavioral problems. The Conner’s Parent Rating Scales was used to assess symptoms of hyperactivity/impulsivity and conduct problems. The health-related quality of life (HRQoL) was assessed using the Pediatric Quality of Life Inventory 4.0 Generic Core Scale. Performance status was assessed using the Lansky play-performance scale and Karnofsky performance scale. The effects of basal ganglia lesions on these scores were examined.Results: Patients with basal ganglia iGCTs (n = 10) had more behavioral problems (attention problems, aggressive behavior, learning problems, hyperactivity index), social function impairment, anxiety/depression, and poorer HRQoL compared to patients with non-basal ganglia iGCTs (n = 20). There was no significant difference in the Lansky play-performance/Karnofsky performance scale scores.Conclusion: This study demonstrates the effects of basal ganglia lesions on behavioral and emotional outcomes, social functions, and HRQoL of patients with iGCTs. The results may help to understand the function of basal ganglia and provide evidence for the benefit of early psychological intervention to improve the treatment for this rare disease.Keywords: intracranial germ cell tumors, pediatrics, The Child Behaviour Checklist, The Conner’s Parent Rating Scales, health-related quality of life